Population dynamics of herbivorous insects in polluted landscapes - Kozlov Mikhail V (Elsevier, 2025)
Environmental pollution is one cause of insect decline in the Anthropocene, but the underlying mechanisms remain obscure due to a paucity of pollution-impact studies on insects that address density-dependent processes. Long data series (19-26 years) are available only for a few species monitored around two industrial polluters in north-western Russia. A particularly exciting current finding is that industrial pollution determines the relative strength of rapid (stabilising) and delayed (destabilising) density dependence operating on a herbivore population. Most studies address acute effects of traditional pollutants (e.g. sulphur dioxide and trace elements) and nitrogen deposition on agricultural pests, whereas the effects of realistic concentrations of ozone, particulate matter and emerging pollutants on insects feeding on noncultivated plants are unknown. The accumulated evidence remains insufficient to predict the effects of pollutants of global concern on the population dynamics of herbivorous insects.